AB0426 Calcium intake in algerian rheumatoid arthritis patients. A multicenter study. (23rd January 2014) - Slimani, S.; Abbas, A.; Ben Ammar, A.; Kebaili, D.; Ali, E.H.; Rahal, F.; Dahou-Makhloufi, C.; Brahimi, N.; Abtroun-Benmadi, S.; Ladjouze-Rezig, A.
Abstract : Objectives: To determine the adequacy of calcium intake in an Algerian cohort of rheumatoid arthritis (RA) patients. Methods: Of 249 RA patients followed in 11 centres, 139 patients accepted to participate in an evaluation of calcium intake at inclusion (22 men, 117 women, mean age 52.7±14.4 years). All patients satisfied the 2010 ACR/EULAR criteria for the diagnosis of RA. Their calcium intake was evaluated by Fardellone questionnaire and compared with recommended calcium intake guidelines of the Institute of Medicine (1000mg/d for adults <50 years and men <71 years, 1200mg for women ≥51 years and men ≥71 years). Information on disease activity, functional status and drug therapy has been recorded at baseline. Statistical analysis has been realised, mainly ANOVA tests and tests of correlation. Results: Mean calcium intake was 408±141mg/d. No patient had an intake of calcium >1000mg/d, and only one person received >800mg/d. The percentage of patients who were supplemented with calcium and vitamin D (1000mg + 800IU) was 52.5%. Male patients had significantly reduced intake of calcium compared with females (350mg/d vs 418mg/d, p =0.038). Other identified risk factors for low calcium intake were higher age ( r =0.208, p =0.015), lower education level ( r =0.264, p =0.002), higher CRP ( r =0.328, p <0.0001). However, there was no variation in calcium intake according to the current DMARD, the type of housing, DAS28, hypertension and diabetes, erosions and HAQ. Conclusions: 100% of our patients do not receive the recommended calcium intake. Only 52.5% are calcium/vitamin D supplemented. Risk factors are male sex, higher age, low education levels and high CRP. Patients with RA should receive dietary education associated with supplementation to bring their intake of calcium to the recommended guidelines. Disclosure of Interest: None Declared